MODEL INTEGRATIF KONSEPTUAL DAN PRODUKSI MEDIA PEMBELAJARAN BERBASIS TIK UNTUK MENINGKATKAN INTERAKTIVITAS DAN KUALITAS PEMBELAJARAN - Wahidin Wahidin (CV. Lafadz Jaya, 2026)
This study aims to analyze an integrative model of Information and Communication Technology (ICT)-based learning media in improving interactivity and the quality of 21st-century learning. The research used a qualitative approach through literature review and observation at SMK Kuala Kapuas. Data were collected from journals, books, and scientific articles related to educational technology and digital learning. The results show that ICT-based learning media improve student engagement, classroom interactivity, learning motivation, and critical and collaborative thinking skills. The use of videos, multimedia, simulations, and e-learning platforms also supports more active and effective learning. However, challenges remain, including limited teacher digital competence and technological facilities. Therefore, continuous training and ICT infrastructure support are needed to optimize digital learning.